PENGEMBANGAN PERANGKAT PEMBELAJARAN MODEL KOOPERATIF TIPE TEAMS GAMES TOURNAMENT MENGGUNAKAN PERMAINAN ULAR TANGGA PADA MATERI TATA SURYA KELAS VII SMP - Pebrianti, Yopa; Maaruf, Zuhdi; Islami, Nur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The type of team games tournament cooperative model learning device usingsnakes and ladders game on solar system material is a learning device in the form oflesson plans, LKPD and Formative Tests combined with the type of team gamestournament cooperative model using snakes and ladders game. These study aims are todevelop learning tools as well as determine the validity of these learning devices. Thelearning devices developed are expected to be media for teachers to convey solarsystem material easily, to make students understood solar system material easily, and toimprove the science learning process in junior high school. The development researchmodel used is the 4D development model (Define, Design, Development, andDisseminate). The research was carried out only until the development stage. Theinstrument used in this study was a validation sheet filled out by 3 validators. Validationresults of the learning devices obtained are valid in the high category with a score of3.25. Therefore, the learning devices developed are suitable for use as learning tools inschools. These learning devices are recommended for teachers. Other research relatedto implementation and development through android applications is still needed.Keywords: Learning Devices, Team Games Tournament Type Cooperative Model.